Correlation of irisin with lipid profile in type 2 diabetes mellitus - Wahengbam Diana Devi,; Oinam Prabita Devi,; Ursula Khwairakpam,; Takhelmayum Paras Singh, (Asian Journal of Medical Sciences, 2025)
Background: Irisin, a novel adipo-myokine, improves insulin sensitivity by browning of white adipose tissue and also promotes pancreatic β-cell proliferation. Irisin was seen to have great therapeutic potential in treating type 2 diabetes mellitus (T2DM) patients. Aims and Objectives: Our study aimed to estimate the levels of serum irisin, lipid profile, and fasting blood sugar (FBS) in T2DM cases and healthy controls and to find any correlation among them. Materials and Methods: We conducted a case–control study on 40 T2DM patients and 40 healthy controls. Enzyme-linked immunosorbent assay was employed for the estimation of serum irisin level, estimation of FBS by glucose oxidase-phenol 4 amino phenazone method (GOD/PAP), and lipid profile by enzymatic colorimetric method. Results: Irisin was found to be lesser (P=0.00) in T2DM cases (14.5±8.6 ng/mL) as compared to controls (28.4±3.9 ng/mL). In T2DM cases, serum irisin was inversely correlated with FBS levels (r=−0.32, P=0.04), FBS was correlated directly with total cholesterol (T-Chol) (r=0.216, P=0.180), triglyceride (TG) (r=0.289, P=0.071), and low-density lipoprotein (LDL) (r=0.325, P=0.041) and negatively correlated (r=−0.269, P=0.094) with high-density lipoprotein (HDL) levels. Whereas irisin levels showed negative correlation with T-Chol (r=−0.294, P=0.066), TGs (r=−0.237, P=0.140), and LDL (r=−0.341, P=0.031) and positive correlation with HDL (r=0.238, P=0.139) levels. Conclusion: Our study showed that the level of serum irisin was decreased in T2DM patients significantly when compared with controls. Irisin improves lipid profile and FBS levels in T2DM cases, hence it may be essential as an adjunctive therapeutic target in the management of T2DM.